Two new Peripatopsis species (Onychophora: Peripatopsidae) from the Western Cape province, South Africa - Mcdonald, Dane E.; Ruhberg, Hilke; Daniels, Savel R. (Zootaxa, 2012)
A recent study based on the mitochondrial cytochrome c oxidase subunit I (COI) and the nuclear 18S ribosomal RNA (18SrRNA) gene sequences from the widely distributed Cape velvet worm species Peripatopsis capensis (Grube, 1866) revealed thepresence of three distinct, geographically exclusive clades characterised by marked sequence divergence values. Two of thethree clades were recognised as novel species and are described in the present manuscript. Gross morphology and scanningelectron microscopy (SEM), in conjuction with the genetic data, were used to discriminate the species. Two new species, P.lawrencei sp. nov. and P. overbergiensis sp. nov., are described and compared with P. capensis sensu stricto. The implications of these results on the conservation management are discussed.